2011
DOI: 10.1177/1057567711417179
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Comparison of Gangs in the United States and Trinidad and Tobago

Abstract: This study compares the scope and nature of the gang problem in two communities: one in the United States and one in Trinidad and Tobago, a small-island developing state in the eastern Caribbean that has experienced a serious outbreak of violence over the past decade. Data drawn from surveys of adult arrestees reveal that among respondents, 3.2% of those in the U.S. sample and 5.1% of those in the Trinidad sample reported being a member of a gang. While there were a number of similarities between the two sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Fieldwork in Trinidad has revealed that some families turn to neighborhood gang leaders to discipline their children (Katz & Maguire, 2015). This occurs in a context in which gangs are more powerful and violent than U.S. street gangs (Katz, Maguire, & Choate, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fieldwork in Trinidad has revealed that some families turn to neighborhood gang leaders to discipline their children (Katz & Maguire, 2015). This occurs in a context in which gangs are more powerful and violent than U.S. street gangs (Katz, Maguire, & Choate, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Eurogang survey comes from the Eurogang Project and consists of a questionnaire constructed to inventory youth groups in specific areas by polling those who are familiar with them—such as police officers—and includes questions that systematically capture group size, durability, membership demographics, street orientation, and association with illegal activity (Decker & Weerman, 2005). It has been tested extensively and applied in various forms in Europe, the United States, and the Caribbean (Decker & Weerman, 2005; Esbensen & Maxson, 2012; Katz, Maguire, & Choate, 2011). As compared with traditional methods of gang study, which tend to be ethnographic in nature, the Eurogang Survey allows for the collection of information that is comparable across time and geographic locales (Decker & Weerman, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately, 90 percent of gangs in Trinidad and Tobago claim turf/territory (Deosaran, 2008;Katz, Maguire, & Choate, 2011;Townsend, 2009). Trinidad and Tobago's Anti-Gang Act No. 10 (2011) defines a gang as "a combination of two or more persons, whether formally or informally organized which, through its membership or through an agent engages in a gangrelated activity" (Hill, 2013, p. 50).…”
Section: Gang Activity In Trinidad and Tobagomentioning
confidence: 99%
“…and approximately twice as likely to have ever been arrested for a property offense, sex crime or other crime" (Katz & Maguire, 2015 p. 189). A study of arrestees in the Port of Spain area revealed that gang members are significantly more likely than non-gang members to report being unemployed prior to their arrest (61.2 percent and 23.8 percent respectively) (Katz, Maguire, Choate, 2011). Additionally, 38.1 percent of gang members note they receive their income from legal and illegal means, while 19 percent report no source of income (Katz, Maguire, Choate, 2011).…”
Section: Gang Activity In Trinidad and Tobagomentioning
confidence: 99%